2012
DOI: 10.3389/fnhum.2012.00121
|View full text |Cite
|
Sign up to set email alerts
|

The role of consciousness in cognitive control and decision making

Abstract: Here we review studies on the complexity and strength of unconscious information processing. We focus on empirical evidence that relates awareness of information to cognitive control processes (e.g., response inhibition, conflict resolution, and task-switching), the life-time of information maintenance (e.g., working memory) and the possibility to integrate multiple pieces of information across space and time. Overall, the results that we review paint a picture of local and specific effects of unconscious info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 184 publications
(266 reference statements)
6
92
0
Order By: Relevance
“…The second question that we addressed was related to the extent to which nonconscious stimuli can trigger prediction error responses, as measured with EEG. Over the last 20 years, we and others have shown that nonconscious information processing is rather sophisticated 57,58 , and that a diverse range of high-level cognitive processes can unfold unconsciously, including motivational processing [59][60][61] , semantic processing 62,63 , decision making 61,64 and cognitive control 65,66 . Interestingly, in Experiment 2 we found evidence that predictions that are violated by a nonconscious stimulus trigger a stronger negative fronto-central ERP component than predictions that are confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The second question that we addressed was related to the extent to which nonconscious stimuli can trigger prediction error responses, as measured with EEG. Over the last 20 years, we and others have shown that nonconscious information processing is rather sophisticated 57,58 , and that a diverse range of high-level cognitive processes can unfold unconsciously, including motivational processing [59][60][61] , semantic processing 62,63 , decision making 61,64 and cognitive control 65,66 . Interestingly, in Experiment 2 we found evidence that predictions that are violated by a nonconscious stimulus trigger a stronger negative fronto-central ERP component than predictions that are confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, new findings have challenged these traditional views by showing that 'high-level' functions of the prefrontal cortex such as conflict-monitoring, response inhibition and error detection can unfold without conscious awareness (D'Ostillio and Garraux, 2012;Nieuwenhuis et al, 2001;Sumner et al, 2007;van Gaal et al, 2008;van Gaal et al, 2011). To examine the influence of unconscious processing on cognitive control functions most studies have used masked-prime paradigms (see review by van Gaal et al, 2012). Generally, in these tasks participants have to respond to a target that is rapidly followed by a prime stimulus that can either facilitate or interfere with the response to the target.…”
Section: Introductionmentioning
confidence: 96%
“…Generally, although several high-level cognitive processes can be influenced by subliminal stimuli they are likely not executed in the same way as during their conscious versions [2,15]. Influential models as well as experimental data suggest that consciousness is required for multiple-step rule-based algorithms, for example in doing mental arithmetic or performing grammatical language operations [16][17][18].…”
Section: Introductionmentioning
confidence: 99%